Change in prosocial development following adversity exposure among U.S. Mexican youth - Carlo, Gustavo; White, Rebecca; Curlee, Alexandra; Tein, Jenn-Yun; Partovi, Roushanac; Knight, George; Gonzales, Nancy (Frontiers in Developmental Psychology, 2024)
Altruistic prosocial behaviors (i.e., actions primarily intended to benefit others with little to no regard for self-benefit) are of special interest to researchers interested in growth in character strengths following exposure to adversity and trauma (referred to as the altruism-born-of-suffering hypothesis). The present study was designed to examine this hypothesis. Changes in prosocial behaviors following trauma exposure and whether problem-focused coping and familism facilitated prosocial behaviors were investigated in U.S. Mexican youth. 749 Mexican-origin students (initial M age = 10.42 years, SD = .55; 48.9% girls) from the U.S. Southwest completed surveys from 5th grade to early adulthood. U.S. Mexican girls who reported earlier trauma exhibited increases in altruistic behaviors into young adulthood but only when they reported relatively high levels of familism values in middle adolescence. A similar trend pattern was found for U.S. Mexican boys but only when they expressed relatively high levels of problem-focused coping in middle adolescence. There was other evidence of significant relations between both familism and problem focused coping and prosocial behaviors in these youth. Findings demonstrate the potential for prosocial development across adolescence to young adulthood among trauma-exposed youth from a U.S. ethnic/racial minority background.